Augmented Reality (AR) as a Learning Tool for Computer Engineering Technical Skills - Lubis, Junaidi H.; Maimunah, Dewi (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
Augmented Reality (AR) has emerged as a transformative tool in technical education, particularly in computer engineering. This study evaluates AR’s effectiveness in enhancing practical skills through a mixed-methods approach involving 60 students divided into an AR-trained experimental group and a control group using traditional methods. Quantitative analysis revealed a significant improvement in post-test performance for the AR group (M = 88.1, SD = 6.3) compared to the control group (M = 75.3, SD = 8.1), with a large effect size (Cohen’s *d* = 3.14). Qualitative findings highlighted reduced anxiety, deeper conceptual understanding, and higher engagement among AR users. Despite challenges such as hardware requirements and content development, the study suggests that AR integration, coupled with instructor training, can significantly enhance technical education. Recommendations include institutional investment in AR tools and further research on long-term skill retention and scalability. The findings affirm AR’s potential as an immersive and interactive learning medium, bridging the gap between theory and practice in engineering education.